Обеспечение динамических показателей электропривода на основе двигателя с катящимся ротором - Кулинченко, Георгий Васильевич; Масленников, Андрей Михайлович; Багута, Виктор Анатольевич; Дунев, Алексей Александрович (НТУ "ХПИ", 2015)
Проанализированы основные факторы, обеспечивающие увеличение вращающего момента двигателя с катящимся ротором. На основе выбранного направления исследований сформулированы требования к системе управления двигателем. Разработанная схема управления позволяет оптимизировать параметры электропривода запорно-регулирующей арматуры. Полученные результаты показали улучшение динамических показателей электропривода на основе двигателя с катящимся ротором.

Main factors affecting the value of rolling rotor motor torque, taking into account the distribution of the magnetic induction in the air gap of the contact point of the rotor and stator are represented. Ways for increasing of rolling rotor motor torque to improve its dynamic performance are selected. The control scheme of rolling rotor motor windings switching with the usage of microprocessor coil current control are developed. An experimental research of rolling rotor motor control system with different modulation types and control pulses forms was carried out. That let to improve an electric drive dynamic and raise the rolling rotor motor torque on 18 %.
Electric drive dynamic performance providing based on a rolling rotor motor
Keywords: магнитная система; управление двигателем; широтно-импульсная модуляция; вращающий момент двигателя; запорно-регулирующая арматура; magnetic system; rolling rotor motor; control system; pulse width modulation